If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(1 + -1x) = 3x + 2 (1 * 5 + -1x * 5) = 3x + 2 (5 + -5x) = 3x + 2 Reorder the terms: 5 + -5x = 2 + 3x Solving 5 + -5x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + -5x + -3x = 2 + 3x + -3x Combine like terms: -5x + -3x = -8x 5 + -8x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + -8x = 2 + 0 5 + -8x = 2 Add '-5' to each side of the equation. 5 + -5 + -8x = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -8x = 2 + -5 -8x = 2 + -5 Combine like terms: 2 + -5 = -3 -8x = -3 Divide each side by '-8'. x = 0.375 Simplifying x = 0.375
| 12x-18=34 | | 4xy-2xz= | | 3(x-5)+2=4(x-1) | | 2lnx(1/x)-x=0 | | 1.2x-4.3=1.7 | | 2x+36=400 | | -4x+14=-10 | | 2b-9+5b=4b+6 | | -8v=1 | | y=9+19x | | 7x+x+(x+3)=39 | | 4u+2v-7v+2u+12v-5u= | | (1-w)(4w-9)=0 | | 15x^3+21x^2=0 | | 0=3+5x+x^2-x^3 | | 5.6=1.1x+1.2 | | 7tan^2x-7=0 | | Ln(x+7)=(3x-5) | | 6x+49=28x+9 | | 2(3x+4)+5x=-1 | | 9k-1=15 | | Ln(x+7)=ln(3x-5) | | (9y-2)(3y+5)= | | Log(7x)=3.5 | | E*-3x=7.1 | | 3t-4=4t+16 | | 3x+31=12x-559 | | 17y=3x-19 | | (9+9)=(8-8) | | 10x-63=11 | | 8x^2-9x+k=0 | | 7x-2x-3x+2.73=4.49 |